2006
DOI: 10.1111/j.1528-1167.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Thalamic Diffusion Abnormalities in Children with Temporal Lobe Epilepsy

Abstract: Summary:Purpose: Previous studies using diffusion MRI in patients with temporal lobe epilepsy have shown abnormal water diffusion in the hippocampus. Because thalamus and lentiform nuclei are considered important for the regulation of cortical excitability and seizure propagation, we analyzed diffusion tensor imaging (DTI) abnormalities in these subcortical structures and in hippocampus of children with partial epilepsy with and without secondary generalization.Methods: Fourteen children with partial epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 41 publications
9
62
0
2
Order By: Relevance
“…Second, both the hippocampus and thalamus play significant roles in seizure initiation, modulation, and propagation (Bertram et al, 2001;Guye et al, 2006;Norden & Blumenfeld, 2002). Third, neuroimaging studies have confirmed that the thalamus is affected in patients with unilateral TLE (Bonilha et al, 2005;Dreifuss et al, 2001;Juhasz et al, 1999;Kimiwada et al, 2006;Natsume et al, 2003). Finally, the thalamus is posited to play an important role in both memory and nonmemory cognitive domains (Crosson, 1992;Johnson & Ojemann, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, both the hippocampus and thalamus play significant roles in seizure initiation, modulation, and propagation (Bertram et al, 2001;Guye et al, 2006;Norden & Blumenfeld, 2002). Third, neuroimaging studies have confirmed that the thalamus is affected in patients with unilateral TLE (Bonilha et al, 2005;Dreifuss et al, 2001;Juhasz et al, 1999;Kimiwada et al, 2006;Natsume et al, 2003). Finally, the thalamus is posited to play an important role in both memory and nonmemory cognitive domains (Crosson, 1992;Johnson & Ojemann, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies have confirmed that the thalamus is affected in patients with unilateral TLE. Cerebral and metabolic hypoperfusion on positron emission tomography, abnormalities on diffusion tensor imaging and magnetic resonance (MR) spectroscopy, and quantitative MR brain volume and voxelbased morphometry (VBM) abnormalities of the thalamus have been reported (Bonilha et al, 2005;DeCarli et al, 1998;Juhasz et al, 1999;Kimiwada et al, 2006;Sperling et al, 1990). However, findings are mixed about the extent of brain volume loss in the thalamus (ipsilateral or bilateral) relative to other neural structures, and its association with clinical seizure characteristics also remains unclear (Dreifuss et al, 2001;Natsume et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant for BCECTS where the occurrence of seizures is very rare, from one to six over the entire duration of the disease in 70% of cases (Rosser, 2007). Interictal DTI studies in children with epilepsy have mostly been performed in temporal lobe epilepsy, showing reduction of fractional anisotropy in the hippocampus (Kimiwada et al, 2006) and in the white matter tracts ipsilateral to left temporal foci (Govindan et al, 2008), or increased mean-, axial-and radial diffusivity in the temporal and cingulate white matter (Lee et al, 2004;Nilsson et al, 2008). Similarly, the coefficient of diffusion (ACD), which is often used interchangeably with mean diffusivity, increased interictally in the epileptogenic hippocampus of adult patients with temporal lobe epilepsy (Kantarci et al, 2002;Duzel et al, 2004).…”
Section: Diffusion Changes In Epilepsymentioning
confidence: 99%
“…Water diffusion is altered by the structures of gray matter (12). DWI can be used to evaluate morphological changes in cortical microstructures (13)(14)(15)(16)(17)(18)(19) and can function as a probe to estimate immediate and transient changes in water diffusion that are associated with ischemia (17) or neuronal firing (13,16,19) and delayed and persistent changes that are associated with long-term plasticity in experimental settings (20) or pathological conditions (15,18,21). Here, using DWI techniques, we examined whether subthreshold, low-frequency (<1 Hz) rTMS to the left primary motor cortex (M1), a protocol that induces LTD-like plasticity (22, 23), increased water diffusion in the left M1 and other regions after the end of rTMS.…”
mentioning
confidence: 99%